Neural stem cell-derived small extracellular vesicles: a new therapy approach in neurological diseases - Wang, Mengyao; Chen, Dongdong; Pan, Renjie; Sun, Yue; He, Xinyu; Qiu, Youming; Hu, Yuexin; Wu, Xiangsheng; Xi, Xuxiang; Hu, Rong; Jiao, Zhigang (Frontiers in Immunology, 2025)
Neural stem cells (NSCs) possess pluripotent characteristics, proliferative capacity, and the ability to self-renew. In the context of neurological diseases, transplantation of NSCs has been shown to facilitate neurological repair through paracrine mechanisms. NSC-derived small extracellular vesicles (NSC-sEVs), a prominent component of the NSC secretome, play a crucial role in modulating various physiological and pathological processes, such as regulating the NSC microenvironment, promoting endogenous NSC differentiation, and facilitating the maturation of neurons and glial cells. Moreover, NSC-sEVs exhibit reduced immunogenicity, decreased tumorigenic potential, and enhanced ability to traverse the blood-brain barrier. Consequently, NSC-sEVs present novel therapeutic approaches as non-cellular treatments for neurological disorders and are poised to serve as a viable alternative to stem cell therapies. Furthermore, NSC-sEVs can be manipulated to enhance production efficiency, improve biological activity, and optimize targeting specificity, thereby significantly advancing the utilization of NSC-sEVs in clinical settings for neurological conditions. This review provides a comprehensive overview of the biological functions of NSC-sEVs, their therapeutic implications and underlying molecular mechanisms in diverse neurological disorders, as well as the potential for engineering NSC-sEVs as drug delivery platforms. Additionally, the limitations and challenges faced by NSC-sEVs in practical applications were discussed in depth, and targeted solutions were proposed.